Heat transfer of swirling multi jets impinging system / Amar Zerrout...[et al.] - Zerrout, Amar; Khelil, Ali; Loukarfi, Larbi (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2020)
This work is the subject of an experimental and a numerical study of a system of swirling jets system impinging a plane wall. The experimental test bench comprising three diameter D diffusers, which are 2D distant between the axes, impacting perpendicular plate, by setting the impact height H = 4D. The swirl is obtained by a generator (swirl) of compound 12 fins arranged at 60 ° relative to the vertical placed just at the exit of the diffuser. A portable VELOCICALC PLUS anemometer device at various stations measures the blowing temperature of the swirling jets hitting the plate. The results of this study have shown that, the global jet has the same characteristics as a free jet, close to the obstacle it undergoes a considerable deviation characterized by the weakening of the temperature and the speeds then the development of the jet. The temperature amplitudes decrease, as we approach the plate. The velocity profiles show that velocity changes direction and increases radially. The Nusselt number is moderate at the level of the impact surface ensuring the homogenization of the heat transfer of the plate. The system was simulated numerically by the Fluent program based on the turbulence model (k-epsilon). The latter gave results of temperature and velocity fields having profiles in line with those of experimental results.